2011
DOI: 10.1093/jac/dkr250
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of carriage with methicillin-resistant Staphylococcus aureus: determinants of treatment failure

Abstract: Guideline adherence, especially among those with complicated MRSA carriage, was associated with treatment success. Adding patients with extranasal carriage or dependence in daily self-care activities to the definition of complicated carriage, and treating them likewise, may further increase treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 16 publications
0
31
3
Order By: Relevance
“…These failures are essentially explained by the multiplicity of colonized sites (armpits, groin, throat, etc.) [31]. Furthermore, using mupirocine creates resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…These failures are essentially explained by the multiplicity of colonized sites (armpits, groin, throat, etc.) [31]. Furthermore, using mupirocine creates resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Successful nasal decolonization of S. aureus is difficult to achieve, and S. aureus readily recolonizes the nose, the throat and other sites within one week, commonly with the same S. aureus genotype [811]. Today, nasal mupirocin is the most efficacious regimen of S. aureus eradication from the anterior nares [12, 13]. However, the success rate for eradication of MRSA is low 12 months after decolonization [14].…”
Section: Introductionmentioning
confidence: 99%
“…Acton et al reviewed cases involving the intestinal carriage of S. aureus [10]. Ammeriaan et al reported that one of the causes of treatment failure for MRSA carriers might be due to the presence of strains colonized at extra-nasal sites [11]. Although MRSA infection is decreasing as results of infection control e.g., performing standard precaution, active surveillance culture, and cohorting, outbreak of MRSA strains still occurred.…”
Section: Introductionmentioning
confidence: 99%